SISTEMATIK REVIEW : PERAN TEKNOLOGI DALAM PERIODE PANDEMI, APA YANG DAPAT DIPELAJARI ? - Suhadi Suhadi; Ruwiah Ruwiah (NHM PRESS, 2021)
Changes in the way health care is provided during this pandemic are needed to reduce staff exposure to the sick, cultivate a culture of personal protective equipment (PPE), and minimize the surge of patients in health care facilities. The aim of this systematic review is to identify the role of technology in healthcare during the COVID-19 pandemic. Several databases, such as Google Scholar, PubMed, Wiley Online Library, Cochrane Library, and Science Direct, were used to search for relevant studies. Eight studies were eligible for inclusion with moderate-good quality using CASP. Based on the research design, the included studies used descriptive, quasi-experimental, research and development, RCT, and case-control designs. In the included study, most telehealth and applications were implemented during the COVID-19 pandemic such as texting, telephone, live video conferencing, and smartphone-based applications. For health care providers and patients who are self-isolating, information technology is certainly appropriate in minimizing the risk of COVID-19 transmission. This solution has the potential to prevent all forms of direct physical contact, provide continuous care to the community, and ultimately reduce morbidity and mortality in the COVID-19 outbreak. Therefore, technology such as telehealth is becoming an important tool in care services while keeping patients and health care providers safe during the COVID-19 outbreak